Acute Kidney Injury in Newborns - Silvana Naunova Timovska; Svetlana Cekovska; Katerina Tosheska-Trajkovska (Macedonian Academy of Sciences and Arts, 2015)
Acute kidney injury is common condition in the neonatal intensive care unit and it is associated with poor outcome. The incidence of neonatal AKI is the highest one followed by adults and children, depending on different factors such as the gestational age, birth weight, contributing conditions and the facilities of the neonatal intensive care unit. The aim of the study was to determine the incidence, risk factors and the outcome of the neonatal acute kidney injury.